Online Learning Evaluation In Malang City and Batu To Improve SMK Students Competency - Ema Sumiarti; Rusijono Rusijono; Andi Mariono (Syntax Corporation Indonesia, 2021)
The important role of policy makers is to develop and improve program implementation. The purpose of the study in general is to evaluate the supporting components of the implementation of online learning which include learning facilities at home and parents' attention in learning, the input component of students' initial abilities, and the process components of activeness following online learning in relation to increasing the competence of SMK students in Malang and Batu. The research design uses evaluation research. The research sample involved 240 students of the multimedia expertise program at SMKN 4, 5, 11 Malang City and SMKN 3 Batu. The data analysis technique used in this research was SEM (Structural Equation Modeling) and LISREL. The results of this study are, 1) learning facilities at home have a direct effect on students' initial abilities, student activity. 2) parents' attention in learning has a direct effect on students' initial ability and student competence, and has an indirect effect on student learning activeness and competence.